Limnology of a lateral lagoon system connected to a Neotropical reservoir (Rosana reservoir, São Paulo/Paraná, Brazil) - Ferrareze, Mateus [UNESP]; Nogueira, Marcos Gomes [UNESP]; Sartori, Luciana [UNESP] (My University, 2014)
The aim of this work was to perform a comparative analysis of four lateral lagoons and of the main channel of the Rosana Reservoir (Paranapanema river), southeast Brazil. The fieldwork was conducted during dry and rainy periods of 2004 and 2005. The analyzed variables were chlorophyll a, turbidity, total phosphorus, total nitrogen, dissolved nutrients (ammonium, nitrate, nitrite, phosphate and silicate), Secchi disk transparency, suspended solids, temperature, pH, dissolved oxygen and electrical conductivity. Intense summer rainfall provided a high input of allochthonous material into the system, resulting in conspicuous changes - high turbidity and nutrient concentrations and low transparency, especially in the reservoir channel. The cluster analysis showed a clear segregation between the reservoir sampling site and the lagoons. The results evidenced the strong influence of regional factors on the limnological structure and functioning of these environments. The alternation between dry and rainy periods changes significantly the characteristics of the main channel and lagoons, mainly due to the contribution of tributaries. Spatially, the system exhibited a remarkable limnological variability. This shows the need to consider these distinct habitats in regional conservation strategy, presently focused on terrestrial habitats.

O objetivo desse estudo foi realizar uma análise comparativa de quatro lagoas laterais e do canal principal do reservatório de Rosana (rio Paranapanema, Brasil). O trabalho de campo foi realizado no período de setembro e novembro de 2004 e janeiro, março, maio e agosto de 2005. As variáveis analisadas foram clorofila a, turbidez, fósforo e nitrogênio total, nutrientes dissolvidos (amônio, nitrato, nitrito, fosfato e silicato), transparência do disco de Secchi, sólidos em suspensão, temperatura, pH, oxigênio dissolvido e condutividade elétrica. As chuvas de verão forneceram grande quantidade de material alóctone ao sistema, o que resultou em mudanças conspícuas - elevada turbidez e altas concentrações de nutrientes, e diminuição da transparência, especialmente no canal do reservatório. A análise de agrupamento mostrou clara a distinção entre o ponto do reservatório e as lagoas laterais. Os resultados evidenciaram a forte influência dos fatores regionais para a estrutura e funcionamento limnológico desses ambientes. A alternância entre períodos de seca e chuva muda significativamente as características do canal do reservatório e das lagoas, principalmente pela contribuição dos rios tributários. Espacialmente, o sistema apresentou uma notável variabilidade limnológica. Isso demonstra a necessidade de se considerar estes habitats em estratégia de conservação regional, focada atualmente nos ecossistemas terrestres.
Limnologia de um sistema de lagoas laterais conectadas a um reservatório Neotropical (reservatório de Rosana, Estado de São Paulo/Paraná, Brasil)
Keywords: Floodplain; Nutrients; Paranapanema river; Limnological variables; Spatial variability; Eutrophication; Lagoas marginais; Nutrientes; Rio Paranapanema; Variáveis limnológicas; Variabilidade espacial; Eutrofização